White River Park: Indianapolis, Indiana (Oz, 1984)
White River Park originated as a reclamation project for Indianapolis and the state of Indiana. While it is intended to bring recognition, revenue, and rejuvenation to downtown Indianapolis, it will also be a park having enough places within it to attract many different kinds of people, at many different times...